Novel Osteo Refurbishment Method and Choice of Colouring Materials for Anatomy Specimens - Dibakar BORTHAKUR; Rajesh KUMAR; Neerja RANI; Rima DADA (Medeniyet Medical Journal)
Objective: The introduction of competency-based medical education curriculum and a shifted focus towards self-directed learning (SDL) in medical schools across the world has necessitated a reduction of didactic teaching hours. Museum specimens are an indispensable tool in anatomy teaching and can play a pivotal role in fostering and reinforcing SDL. Coloring of specimens makes it attractive and facilitates understanding anatomy. The aims of this study were: (1) weigh up the two commonly used coloring materials in anatomy viz. acrylic paint and nail polish; and (2) to assess the perception of anatomy students towards a Novel Osteo Refurbishment Method (NORM) for restoration of partially damaged osteology specimens. Methods: Undergraduate and postgraduate students of anatomy were recruited in the study. Participants responded to a 5-point Likert scale questionnaire. Obtained data were analyzed using Microsoft Excel version 2019. For a comparison of the two coloring agents Mann-Whitney U test was applied to the responses toward the Likert scale-based questionnaire. P-value <0.05 was considered significant. Results: Out of 318 study participants, 63.7% and 36.3% of the respondents were male and female, respectively. 90.5 % were new entrants to university and the remainder 9.5% had a prior university degree. Students found the acrylic paint to be a better coloring agent and they also opined that NORM generated refurbished osteology specimens could serve as a useful selflearning tool. Acrylic paint was found to be more suitable as compared to nail polish with significant p-value in most of the parameters tested. Conclusions: Acrylic colour holds a good place in coloring both specimens and models in anatomy. Nail polish can be an alternative but with some noted disadvantages. The initial experience with NORM yielded encouraging results with potential practical utility.